1999
DOI: 10.1143/jjap.38.863
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Polyethylene Thin Films Using Synchrotron Radiation Ablation

Abstract: A large set of calculations has been carried out providing a basis for diagnostics of fusion plasmas through emission resulting from radiative de-excitation following charge transfer between hydrogen and highly charged argon ions, so-called argon charge exchange recombination spectroscopy. These results have been obtained using the classical trajectory Monte Carlo (CTMC) method to treat charge transfer to states with principal quantum numbers up to 30 or more. Nine collision energies between 13.3333 and 250 ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…5) show the evolution of H (2 amu), F (19 amu), and HF (20 amu) species, in accordance with previous studies [10], [11], [15]. The data also reveal that HF molecules are produced more readily than F. The appearance of HF was delayed by a few seconds at the beginning of irradiation, and it continued for more than ten seconds after the X-ray beam was turned off.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…5) show the evolution of H (2 amu), F (19 amu), and HF (20 amu) species, in accordance with previous studies [10], [11], [15]. The data also reveal that HF molecules are produced more readily than F. The appearance of HF was delayed by a few seconds at the beginning of irradiation, and it continued for more than ten seconds after the X-ray beam was turned off.…”
Section: Resultssupporting
confidence: 89%
“…In situ mass spectroscopy revealed the evolution of H, H , and HF under UV and excimer laser irradiation, while under the ion beam irradiation, in addition to H and HF, the emanation of F was detected. In a recent work [15] on the effect of soft X rays from a compact synchrotron light source on PVDF, the mass spectroscopy results showed a predominant evolution of HF species. The residual film formed in the irradiated region exhibited higher electrical conductivity and lower solubility compared to pristine samples.…”
Section: Introductionmentioning
confidence: 98%
“…However, Langmuir or LB film formation of poly(ethylene) (PE) was not successful and crystallization studies were not reported. Some thin film studies have been done using medium-density PE [ 32 , 33 ]. The issue regarding PE Langmuir/LB film formation is the lack of polar groups in the repeating unit.…”
Section: Introductionmentioning
confidence: 99%
“…Because of excellent dielectric and tribologic properties, PE thin films have many current and potential applications. Methods of PE thin film preparation include molding, solution casting 2 or dipping, 3 direct 4 or ionization-assisted 5 thermal evaporation in vacuum, synchrotron radiation ablation, 6 and radiofrequency magnetron sputtering. 7 In most reported thin film work, films were 100-1000 nm thick.…”
Section: Introductionmentioning
confidence: 99%